Systematic position of Dinidoridae within the superfamily Pentatomoidea (Hemiptera: Heteroptera) revealed by the Bayesian phylogenetic analysis of the mitochondrial 12S and 16S rDNA sequences - Lis, Jerzy A.; Lis, Paweł; Ziaja, Dariusz J.; Kocorek, Anna (Zootaxa, 2012)
Mitochondrial 12S and 16S rDNA sequences of five species of Dinidoridae Stål, 1868, a largely Paleotropical family, and 16 other shield bugs (Pentatomoidea) were studied. This was the first molecular examination of the systematic position of this family within the superfamily Pentatomoidea using more than a single dinidorid species. Phylogenetic trees obtained from the Bayesian inference of 12S and 16S sequences of these mitochondrial DNA, identified Dinidoridae as the monophylum and a sister group to the Tessaratomidae. Moreover, results of the study suggested a close molecular affinity of the genus Eumenotes to representatives of the subfamily Dinidorinae, which contradicts all previous morphological analyses that placed it within the subfamily Megymeninae. We suggest restoring taxonomic status of the tribe Eumenotini and removing it from the synonymy of Megymenini, leaving the genus with no subfamilial assignment for the moment.